How Can the Construction of a Scrapbook Increase Seventh Graders’ Intrinsic Motivation in an EFL Public Institution? (2019)
ABSTRACT: This action research was aimed at increasing seventh graders’ intrinsic motivation through the construction of a scrapbook at a public institution in Bello. Data was collected through a journal, self-assessments, a questionnaire, scrapbook entries made by the students, and an interview to the teacher. Data analysis showed the potential effectiveness of this strategy because of the creative process implied in it, the memories that students can bring when building it, and the involvement in their learning process. It would be interesting to see the results of this same strategy throughout a whole school year to be submitted as a final project, or in smaller EFL courses.